Towards Alternative Energy Sources: Is it Time to Switch to Nyamplung? - Siagian, Abdhy Walid; Daffa Alghazali, Muhammad Syammakh (Udayana Journal of Law and Culture, 2023)
Nyamplung  is one of the six priority non-timber forest products in Indonesia. This type of mangrove has a high yield of oil as a raw material biofuel with a 40-70% higher percentage than other plants, such as oil palm, whose percentage is only 46-54%. This article examines Indonesia's commitment to accelerate the transition to new and renewable energy through biofuels to meet the national electricity supply. In addition, it conducts an economic calculation of  nyamplung  as alternative energy for biofuels. The writing of this article reflects an economic analysis of law that combines legal analysis based on norms, guidelines, and plans as stipulated in Indonesian laws and regulations and international instruments and economic analysis referring to relevant data and sources. This article concludes that  nyamplung  may serve as an alternative energy source to fulfill future national energy needs, which aligns with efforts to achieve a sustainable environment. Despite laws and policies on national energy supporting any efforts to complement and substitute current energy sources, the utilization of   nyamplung   has yet to be optimized as a biofuel.